Toxoplasma gondii and Neospora caninum infections in synanthropic rodents from Argentina - Dellarupe, Andrea; Fitte, Bruno; Pardini, Lais Luján; Campero, Lucía María; Bernstein, Mariana; Robles, Maria del Rosario; Moré, Gastón Andrés; Venturini, María Cecilia; Unzaga, Juan Manuel (Revista Brasileira de Parasitologia Veterinária)
Toxoplasma gondii and Neospora caninum are closely related coccidian parasites (phylum Apicomplexa). This is the firststudy from urban synanthropic rodent species that involved serological and molecular diagnosis of T. gondii and N. caninuminfection, and genotyping of T. gondii in Argentina. A total of 127 rodent samples were trap captured: Mus musculus (n = 78),Rattus norvegicus (n = 26) and Rattus rattus (n = 23). Antibodies against T. gondii and N. caninum were detected by IFAT in32.8% (40/122) and 0.8% (1/122) of rodent samples, respectively, demonstrating contact with these protozoans. Additionally,T. gondii DNA was detected in 3.3% (4/123) of rodent central nervous system samples and 2 samples were genotyped bymultilocus nPCR-RFLP. Neospora caninum DNA was not detected by PCR. The 2 genotyped samples were type III allelefor all markers except for SAG-1 (type I for Rat1Arg and type II/III for Rat2Arg) and were identified as #48 and #2 (likely)according to the allele combinations reported on Toxo DB (Toxo-DB). The results of the present study revealed a widedistribution of T. gondii and less for N. caninum, in synanthropic rats and mice in the studied area. Toxoplasma gondii e Neospora caninum são parasitas coccídeos intimamente relacionados (filo Apicomplexa). Este é o primeiro estudo de espécies de roedores sinantrópicos urbanos, o qual envolveu diagnósticos sorológicos e moleculares da infecção por T. gondii e N. caninum e genotipagem de T. gondii na Argentina. Um total de 127 amostras de roedores foram obtidas: Mus musculus (n = 78), Rattus norvegicus (n = 26) e Rattus rattus (n = 23). Anticorpos contra T. gondii e N. caninum foram detectados pela IFAT em 32,8% (40/122) e 0,8% (1/122) das amostras de roedores, respectivamente, demonstrando contato com esses protozoários. Adicionalmente, o DNA de T. gondii foi detectado em 3,3% (4/123) das amostras do sistema nervoso central de roedores e duas amostras foram genotipadas por nPCR-RFLP multilocus. O DNA de N. caninum não foi detectado por PCR. As 2 ...